Atomic mapping of structural distortions in 109° domain patterned BiFeO3 thin films. Issue 12 (9th June 2017) - Wang, Wen-Yuan; Zhu, Yin-Lian; Tang, Yun-Long; Han, Meng-Jiao; Wang, Yu-Jia; Ma, Xiu-Liang
Abstract: Abstract : Structural distortions at the nanoscale are delicately linked with many exotic properties for ferroic thin films. Based on advanced aberration corrected scanning transmission electron microscopy, we observe BiFeO3 thin films with variant tensile strain states and demonstrate at an atomic scale the interplay of intrinsic spontaneous structural distortions with external constraints. Structural parameters (the rhombohedral distortion and domain wall shear distortion) under zero (BiFeO3 /GdScO3 ) and 1.5% (BiFeO3 /PrScO3 ) lateral strain states are quantitatively analyzed which are suppressed within a few unit cells near the film/substrate interfaces. In particular, an interfacial layer with asymmetrical lattice distortions (enhanced and reduced out-of-plane lattice spacing) on the two sides of 109° domain wall is resolved. These structural distortions near the film/substrate interface in ferroic thin films reveal intense tanglement of intrinsic distortions of BiFeO3 with external boundary conditions, which could provide new insights for the development of nanoscale ferroelectric devices.